The Legal Implications and Remedies Concerning Revenge Porn and Fake Porn: A Common Law Perspective. - Mania, Karolina (Sexuality & Culture, 2020)
Based on US and British regulations in force, this article offers an overview of legislation of two Common Law countries in the area of modern forms of law infringements focusing on the notions of revenge porn and fake porn. The first part contains definitions and descriptions of the terms 'revenge porn' and 'fake porn', pointing out to the context of the relationship between the dynamic technological development and use of artificial intelligence on the one hand and the regulatory framework failing to meet the current needs on the other. Further, examination is conducted of US and British legislation in force divided into civil and criminal law, indicating legislative gaps as well as the inefficiency of the existing legal solutions and presenting a range of proposals of legislative changes. The considerations have been supplemented with the results of the author's assessment of sociological and statistical research available in source literature carried thus far in the field in question. The following section is dedicated to a comparative assessment of American and British legal solutions based on selected, critical issues. The final parts of the article serve to postulate systemic changes in legislation and is a proposal to introduce out-of-court dispute settlement methods in legal disputes pertaining to the matters discussed herein, and to frame future research directions.